Lessons from the fish: a multi‐species analysis reveals common processes underlying similar species‐genetic diversity correlations. (November 2016) - Fourtune, Lisa; Paz‐Vinas, Ivan; Loot, Géraldine; Prunier, Jérôme G.; Blanchet, Simon
Summary: Species‐genetic diversity correlations (SGDCs) have been investigated over a large spectra of organisms, which has greatly improved our understanding of parallel processes potentially driving both species and genetic diversity. However, there are still few studies comparing SGDCs (and underlying processes) for multiple species sampled over a single landscape. Here, focusing on freshwater fish sampled across a large river basin (the Garonne‐Dordogne river basin, France), we combined a multi‐species approach and causal analyses to (i) assess and compare both α‐SGDCs and β‐SGDCs among species, and (ii) infer processes underlying α‐SGDCs and β‐SGDCs. Genetic, intraspecific diversity was assessed for four sympatric fish ( Barbatula barbatula, Gobio occitaniae, Phoxinus phoxinus and Squalius cephalus ) using microsatellite markers. Species diversity was quantified as species richness using electric fishing, and environmental conditions were thoroughly described for 81 sites. We found significant and moderate positive α‐SGDCs for all four fish species, whereas β‐SGDCs were weaker in strength and positively significant for two of the four species. Causal analyses identified two common variables (geographical isolation and area of available habitats) underlying the α‐SGDC relationships. Although weak, we found that β‐SGDC correlations related to a direct relationship between taxonomic and genomic differentiation, and to the common influence of the abiotic environment acting as a filter on both species and alleles. Our study shows that similar ecological and evolutionary processes related to environmental filtering, migration, drift and colonisation history act for explaining both species and genetic diversity of fish communities.